2014 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) 2014
DOI: 10.1109/vlhcc.2014.6883026
|View full text |Cite
|
Sign up to set email alerts
|

Helping programmers navigate code faster with Patchworks: A simulation study

Abstract: Programmers spend considerable time navigating source code, and we recently proposed the Patchworks code editor to help address this problem. A prior preliminary study of Patchworks found that it significantly reduced programmer navigation time and navigation errors. In this paper, we expand on these findings by investigating the effect of various patch-arranging strategies in Patchworks. To evaluate these strategies, we ran a simulation study based on actual programmer navigation data. Our simulator results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…For example, studies of predictive models of programmer navigation have consistently found that one of the strongest predictors of which code method (i.e., subroutine) a programmer would click in next was how recently he/she had visited the method (i.e., more recently implies more likely) [10,26,29,33,38,45]. Studies have also found that between 82% [16,45] and 95% [33] of programmer navigations were to previously visited methods.…”
Section: Programmer Navigationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, studies of predictive models of programmer navigation have consistently found that one of the strongest predictors of which code method (i.e., subroutine) a programmer would click in next was how recently he/she had visited the method (i.e., more recently implies more likely) [10,26,29,33,38,45]. Studies have also found that between 82% [16,45] and 95% [33] of programmer navigations were to previously visited methods.…”
Section: Programmer Navigationmentioning
confidence: 99%
“…As our main analysis, we used qualitative coding methods to identify where the participants navigated-that is, on which patches they placed their attention-throughout each of their sessions. Following the coding rules from a prior study [16], we coded each time (accurate to a second) a participant moved his/her attention from one patch to another. Additionally, we coded navigation mistakes based on participants' utterances after a navigation, indicating if a navigation did not result in their intended destination.…”
Section: Qualitative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the information seeking behavior of developers on Q&A platforms, we used variation foraging theory [6]- [8], an extension of Information Foraging Theory (IFT) [9]. IFT is a theory of information seeking that has been applied successfully to diverse domains such as documents, the web, user interfaces, and programming [8], [10]- [17]. IFT helps to explain a developer's foraging behavior by relating it to primitive hunting and foraging strategies for food.…”
Section: Introductionmentioning
confidence: 99%